2023
DOI: 10.1172/jci.insight.163306
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor c-Maf deletion improves streptozotocin-induced diabetic nephropathy by directly regulating Sglt2 and Glut2

Abstract: The transcription factor c-Maf has been widely studied and has been reported to play a critical role in embryonic kidney development; however, the postnatal functions of c-Maf in adult kidneys remain unknown as c-Maf null C57BL/6J mice exhibit embryonic lethality. In this study, we investigated the role of c-Maf in adult mouse kidneys by comparing the phenotypes of tamoxifen (TAM)-inducible c-Maf knockout mice (c-Maf flox/flox ; CAG-Cre-ER TM mice named "c-Maf ΔTAM ") with that of c-Maf flox/flox control mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…Moreover, the mechanistic roles of c-MAF in the recovery from acute injury in the intestine promote the differentiation of epithelial cells and the importance of crosstalk between differentiated tuft cells and enterocytes to accelerate long-term intestinal accommodation [21]. While these two studies suggested a requirement for c-MAF in organ injury, we report a protective effect of c-MAF deficiency against diabetes and diabetes-induced nephropathy through c-MAF regulation of the glucose transporters SGLT2 and GLUT2, which are expressed in the proximal tubules of kidneys [22]. In summary, c-MAF deficiency is interesting and has the potential to decrease susceptibility and provide protection against injury and diseases.…”
Section: Roles Of C-mafmentioning
confidence: 54%
See 2 more Smart Citations
“…Moreover, the mechanistic roles of c-MAF in the recovery from acute injury in the intestine promote the differentiation of epithelial cells and the importance of crosstalk between differentiated tuft cells and enterocytes to accelerate long-term intestinal accommodation [21]. While these two studies suggested a requirement for c-MAF in organ injury, we report a protective effect of c-MAF deficiency against diabetes and diabetes-induced nephropathy through c-MAF regulation of the glucose transporters SGLT2 and GLUT2, which are expressed in the proximal tubules of kidneys [22]. In summary, c-MAF deficiency is interesting and has the potential to decrease susceptibility and provide protection against injury and diseases.…”
Section: Roles Of C-mafmentioning
confidence: 54%
“…Subsequently, other st have demonstrated inhibition of the development of the liver sinusoid by specific de of c-MAF in endothelial cells, which induces aberrant expansion of postnatal liver h topoiesis, accelerates excessive proliferation of sinusoidal cells during the postnat riod, and worsens sensitivity of pro-fibrotic effects in the liver to chemical insults Moreover, the mechanistic roles of c-MAF in the recovery from acute injury in the inte promote the differentiation of epithelial cells and the importance of crosstalk betwee ferentiated tuft cells and enterocytes to accelerate long-term intestinal accommod [21]. While these two studies suggested a requirement for c-MAF in organ injury, w port a protective effect of c-MAF deficiency against diabetes and diabetes-ind nephropathy through c-MAF regulation of the glucose transporters SGLT2 and GL which are expressed in the proximal tubules of kidneys [22]. In summary, c-MAF ciency is interesting and has the potential to decrease susceptibility and provide p tion against injury and diseases.…”
Section: C-maf Point Mutation In Human Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that it is likely, that compared to the Sglt1 gene in the skeletal muscle, the DNA for the Sglt2 gene in skeletal muscle may be more tightly wound around it's supporting proteins to form chromatin and this could affect the genes availability for transcription [32]. Additionally, the transcription factors for the Sglt2 gene such as C-Maf [33] may not be present in many tissues which may explain the limited expression of SGLT2 in the body.…”
Section: Discussionmentioning
confidence: 99%